Pengaruh Motivasi terhadap Kinerja Karyawan yang dimediasi Kepuasan Kerja pada PT Panca Perkasa Laksana - Firda Amalia Wijaya; Tjahjani Prawitowati (Ekonomis: Journal of Economics and Business, 2023)
Motivation is the process of giving encouragement to an employee to act in order to achieve the goals of the organization. This study aims to examine the influence of motivation on employee performance by mediating job satisfaction in PT Panca Perkasa Laksana. The sample consisted of 40 Employees working in companies PT Panca Perkasa Laksana in Surabaya, aged 20-60 years and had a minimum of one year of service. The sampling technique uses Saturation sampling. Analysis using structural equating modeling (SEM) on partial least square (PLS) and data collection using a questionnaire in the form of google form. The results of this study indicate that Motivation has a positive and insignificant effect on Employee Performance, Motivation has a positive and insignificant effect on job satisfaction, job satisfaction has a positive and insignificant effect on Employee Performance and Motivation has a positive and not significant effect on employee performance by mediating job satisfaction.